Patrimônio, preservação e políticas públicas: o caso da Estação Ferroviária de Marinhos - Juliana Gazzinelli de Oliveira (2014)
A cultural heritage represents the memory of a time and contributes to build the history of the community. The importance of preserving the historical and cultural heritage can be understood in the memories of the residents. This study analyzes, through the report of the dwellers, the elements that demonstrate the appreciation of the afrodescendants community of Marinhos in Brumadinho, MG, in relation to its railway station. The building, listed as a monument by the government of Brumadinho in 2004, is bad state of preservation and conservation. The memory of the residents who lived through the operation of the station becomes an important power to raise public awareness for their conservation through public policy instrument. The aim of this study was to recover the memory of the population of the community in relation to the railway station and study the existence of public policies for municipal preservation. Semi-structured interviews with residents were analyzed taking as reference the relationship of the individual and the community with the building. The reports showed that the station had an economic, social and affective importance to the community, and so, it is an important heritage to be preserved. With the end of the passenger rail transport, the activities and moments at the station disappeared. It is hoped that the findings sensitize and mobilize the municipality of Brumadinho regarding policies to protect the railway station of Marinhos, contributing to many studies in the area of heritage preservation.